3 - The Return of the Gods? Trends and Implications of the Rising Popularity of Fetish Rituals and Occult Practices Among Nigerian Youth - Nwaka, Jacinta Chiamaka (Africa Development, 2020)
In his seminal 1993 work The Embattled Gods: Christianization of Igboland 1841–1991, Ogbu Kalu argued that the gods of African traditional religion were dislodged from their stronghold but not completely defeated. Could the rising popularity of fetish rituals and occult practices among the Nigerian youth over the last two decades mean the return of these gods? Using historical analytical methodology, this article examines the rising influence of fetish rituals and occult practices among youth in southern Nigeria. It recognises the current attraction of the occult world as a subtle form of youth resistance to financial and social insecurity engendered by the modern state system in Nigeria, as well as youth resistance to the money-making ethos of ‘prosperity gospel’ evangelism. The article argues that, while the surge in youth engagement in ritual and occult practices may appear to be a form of re-traditionalisation, such cultural revisionism can better be described as an instrument of youth resistance.